Pembelajaran Pantun Dan Dampaknya Dalam Pembentukan Karakter Siswa - Sahri Nova Yoga (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
All knowledge, feelings and thoughts of Malay people are internalized through pantun. This classical art of speech contains Malay life experience, wisdom, thoughts, language, arts and culture. Pantun is a forum for expressing thoughts and feelings about the meaning of life, education, human behavior and its relationship with the natural environment. As an effort to maintain the existence of pantun, schools have the responsibility to introduce pantun to the younger generation. The inheritance of culture from one generation to the next can be carried out in interesting and memorable learning. In this digital era, teachers must be able to adapt and synergize with technological advances. So learning rhymes must be varied and technologically literate. Teachers can maximize the use of digital applications to introduce and familiarize themselves with pantun. In this way, learning can keep up with the times and the interests of the younger generation who are very responsive to the rapid development of technology.